THE METHODOLOGY OF DEVELOPING CREATIVE THINKING IN 4TH GRADE STUDENTS BY COMPLETING TIMSS TASKS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The relevance of this article lies in how the state of a fourth-grade student and his psychological feeling changes in mathematics and science lessons, in which students complete TIMSS tasks (especially the mathematical part). Attention is paid to the popular issue of revealing the essence of the most international assessment study of comparative analysis of TIMSS in modern society and in the dominant world powers - the leaders of international research, their merits in their contribution to education and the restructuring of the process, in which special emphasis is placed on the comprehensive development of the personality of a primary school student and his cognitive abilities. The article also describes the results of the TIMSS study and its impact on the development of creative thinking in primary school students. The structure of TIMSS test items is discussed, divided into separate blocks “Knowledge”, “Application” and “Reasoning”. This article is relevant for teachers, educators, and students of primary education.